HOFFMANN’S REMINISCENCES IN THE NOVEL “THE COLLECTOR” BY J. FOWLES (SCIENTIFIC AND METHODICAL MATERIALS TO THE STUDY OF J. FOWLES’ NOVEL “THE COLLECTOR” IN HEI) - Terekhovska, O. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article deals with the artistic echoes of the ideas of the German romantic author E.T.A. Goffman in the novel “The Collector” by the English postmodernist J. Fowles. The aim of the study is to prove that Hoffmann’s concept of dividing people into inhabitants and artists, burghers and creative persons, ordinary and elected ones, i.e., philistines and enthusiasts, found its artistic echo in the images and situations of the novel “The Collector” by J. Fowles; as well as to generalize and adapt scientific and theoretical material on this problem to the students of philology while their preparation for practical and seminar classes. The research methodology is to extrapolate Hoffman’s concept of enthusiasts and philistines to the text of the “Collector”, as well as to determine the confrontation between these two types of people as one of the leading themes of Fowles’ novel. Research results. It is emphasized that Hoffman has divided all his characters into two unequal groups: enthusiasts and philistines. It is established that in Hoffmann’s stories the world of enthusiasts symbolizes full of life existence with all the richness of ideas, emotions, contradictory and complex feelings typical for a search person; the world of philistines, instead, personifies a dim imitation of a real life, i.e. a “mechanized” existence, in which there is no creative impulses, creative initiative. In his works Hoffman warns mankind of the danger of such existence emphasizing the need to protect the world of enthusiasts. It is proved that Hoffman’s thoughts were prophesied. Less than 150 years later, their echo has found its artistic reflection in the works of modern English writer John Fowles, in particular in the novel “The Collector”. In the images of the protagonists Miranda and Frederick Clegg, John Fowles depicted two opposite worlds, which are considered a symbolic continuation of the confrontation of Hoffmann’s enthusiasts and philistines. Miranda represents a modern type of enthusiast, a search person who is choked with emotions and feelings, intuitively realizing that this is the meaning of her life. Clegg generalizes a modern type of a philistine – an ambitious, limited tyrant, full of hidden malice and hatred for those who are spiritually richer and smarter. Hoffman’s warnings have also come to the fore in the fact that philistines can make enthusiasts their victims, as it is illustrated in the novel on the example of the tragic fate of Miranda. Scientific novelty. Reminiscences of Hoffmann’s ideas about the confrontation between enthusiasts and philistines, generalized in the images and types of “The Collector” by J. Fowles, reminding of the eternal antagonism between love and hatred, good and evil, creative living principles and a mundane existence, constitute the scientific novelty of this article. Practical significance. The results of the study can be used for further research of J. Fowles’ literary heritage. The article will be also useful for the students of philology while their preparation for seminars and practical classes.